Activation of PXR by Alpinetin Contributes to Abrogate Chemically Induced Inflammatory Bowel Disease - Yu, Zhilun; Yue, Bei; Ding, Lili; Luo, Xiaoping; Ren, Yijing; Zhang, Jingjing; Mani, Sridhar; Wang, Zhengtao; Dou, Wei (Frontiers in Pharmacology, 2020)
Alpinetin is a naturally occurring flavonoid from the ginger plants. We previously reported the identification of alpinetin as a ligand of human pregnane X receptor (hPXR). The current study investigated the role of alpinetin as a putative PXR activator in ameliorating chemically induced inflammatory bowel disease (IBD). We found that oral administration of alpinetin significantly alleviated the severity of dextran sulfate sodium (DSS)-induced colitis in mice by decreasing the inflammatory infiltration, the levels of the pro-inflammatory mediators and the PXR target genes in the colon. In vitro, alpinetin blocked the nuclear translocation of p-p65 in lipopolysaccharide (LPS)-stimulated RAW264.7 macrophages. Further, alpinetin significantly upregulated PXR target genes and inhibited TNF-α-induced NF-κB-luciferase activity in LS174T colorectal cells; however, this regulatory effects were lost when cellular PXR gene was knocked down. In PXR transactivation assays, alpinetin increased both mouse and human PXR transactivation in a dose-dependent manner. Ligand occluding mutants, S247W/C284W and S247W/C284W/S208W, in hPXR-reporter assays, abrogated alpinetin-induced hPXR transactivation. Finally, alpinetin bound to the hPXR-LBD was confirmed by competitive ligand binding assay and molecular docking study. The current study significantly extends prior observations by validating a PXR/NF-κB regulatory mechanism governing alpinetin’s anti-inflammatory effects in a murine model of IBD.